0 Rajan@2021Guru Asked: April 25, 20212021-04-25T08:43:07+05:30 2021-04-25T08:43:07+05:30In: CBSE Solve for x and y: 6(ax+by)=3a+2b, 6(bx-ay)=3b-2a 0 This question is taken from linear equations in two variables in which we have given two equations 6(ax+by)=3a+2b, 6(bx-ay)=3b-2a and we have to find the variables x and y from the given equations RS Aggarwal, Class 10, chapter 3B, question no 44 class 10 cbselinear equations in two variablesrs aggarwal Share Facebook 1 Answer Voted Oldest Recent MathsMentor Guru 2021-04-27T14:51:57+05:30Added an answer on April 27, 2021 at 2:51 pm Given that 6(ax + by) = 3a + 2b 6ax + 6by = 3a + 2b ——— (1) 6(bx – ay) = 3b – 2a 6bx – 6ay = 3b – 2a ————- (2) On solving (1) a & (2) b, we get 6ax 2 + 6aby = 3a 2 + 2ab 6b 2 x – 6aby = 3b 2 – 2ab ————————————— 6ax^2 + 6b 2 x = 3a^2 + 3b^2 6x(a^2 + b^2) = 3(a^2 + b^2) x = 3/6 x = 1/2. Substitute x = 1/2 in above equations, we get 6ax + 6by = 3a + 2b 6a(1/2) + 6by = 3a + 2b 3a + 6by = 3a + 2b 6by = 2b y = 2b/6b y = 1/3. Therefore the value of x = 1/2 and y = 1/3. 0 Reply Share Share Share on Facebook Share on Twitter Share on LinkedIn Share on WhatsApp Leave an answerLeave an answerCancel reply Featured image Select file Browse Add a Video to describe the problem better. Video type Youtube Vimeo Dailymotion Facebook Choose from here the video type. Video ID Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs". Click on image to update the captcha. Save my name, email, and website in this browser for the next time I comment. Related Questions A boat goes 24km upstream and 28km downstream in 6 hours. It goes 30km upstream and 21km downstream ... Solve the following quadratic equation: √2x²+7x+5√2=0. Solve the following quadratic equation: x²+3√3x-30=0 Solve the following quadratic equation: x²-(√3-1)x+√3=0 Solve the following quadratic equation: x²-3√5x+10=0

Given that 6(ax + by) = 3a + 2b

6ax + 6by = 3a + 2b ——— (1)

6(bx – ay) = 3b – 2a

6bx – 6ay = 3b – 2a ————- (2)

On solving (1) a & (2) b, we get

6ax 2 + 6aby = 3a 2 + 2ab

6b 2 x – 6aby = 3b 2 – 2ab

—————————————

6ax^2 + 6b 2 x = 3a^2 + 3b^2

6x(a^2 + b^2) = 3(a^2 + b^2)

x = 3/6 x = 1/2.

Substitute x = 1/2 in above equations,

we get

6ax + 6by = 3a + 2b

6a(1/2) + 6by = 3a + 2b

3a + 6by = 3a + 2b

6by = 2b

y = 2b/6b

y = 1/3.

Therefore the value of x = 1/2 and y = 1/3.